(untitled) (Indian Journal of Animal Production and Management, 2016)
Poultry being fastest growing segment, estimated to have around 4500 thousand metric tons annual poultry waste production in India. Handling and disposal of this huge waste is a great task for the poultry producers. The experiment was conducted for 90 days during July to September month to investigate the processes taking place during composting with regards to biodegradability of the mixture for efficient waste disposal. Two treatments with 3 replicates using enclosed compost bins (1.2m length × 1.2m width × 1.2m height), T1 was prepared by mixing poultry litter, dead carcass or offals of slaughtered birds and paddy straw (Oryza sativa) as a source of carbon. Sequential layering of dead carcass or offals of slaughtered birds, poultry litter and addition of water was same except the carbon source i.e. paddy straw was replaced by saw dust thus forming second treatment (T2) and were compared with the control group consisting of conventional waste material (T0) which was composed of poultry litter and debris. Physical changes, chemical composition and microbial load of initial ingredients and finished product were recorded during composting. Mature compost weight reduction was higher in treatment mixture T1 (31.6 %) followed closely in T2 (30.1%) than the T0 (10.5%). Volume reduction indicated significant difference between both T1 (41.8 %) and T2 (15.5 %) groups. On day 7 of composting, theT1 and T2 had pH of 8.82 and 8.67 respectively, while approaching to maturity the compost mixture had pH of 8.3 and 8.1 in treatment T1 and T2 respectively. Electrical Conductivity and Total Dissolved Solids had decreasing trend from primary stage to secondary stage. The total organic matter content was reduced at the end of secondary stage and ranged between 19.6 and 21.2 per cent. There was a reduction in total organic carbon content at the end of secondary stage in both the treatments T1 and T2 which was found to be 20.32 and 21.4 per cent respectively. This might be due to loss of organic matter through microbial degradation. At end of composting, the total Nitrogen content of different treatment mixtures ranged between 2.71-3.81 per cent. C: N ratio of different treatment mixtures did not differ significantly at maturity and it ranged between 14.1:1 and 14.5:1. The Ca and P levels of the composted product were increased by 49.8 and 48.2 per cent in treatment containing paddy straw and saw dust respectively. The Total Bacterial Count was numerically higher at the time of loading, reduced at end of primary stage and maintained thereafter. Reduction in lactose fermenter and non-lactose fermenting bacteria was also found till maturity of compost. In conclusion, use of aerobic composting as method of waste disposal is efficient management of poultry farm waste.